2017
DOI: 10.5897/ajps2016.1441
|View full text |Cite
|
Sign up to set email alerts
|

Genotype environment interactions for grain yield in rice under no drought and drought conditions

Abstract: Environments in sub-Saharan Africa fluctuate considerably across sites and seasons. This suggests the importance of assessing genotype x environment interaction (GEI) in cultivar development. The objective of this study was to estimate the magnitude of GEI for rice grain yield and identify high yielding and stable rice genotypes. Fifty six genotypes including 45 F 3 rice populations, their 10 parents and one check were evaluated in 7 x 8 alpha lattice design with two replications under three no drought and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The stable cultivars usually express better yields and have high adaptability across a wide range of environments. Therefore, evaluating different genotypes across different environments or growing seasons helps to identify donor germplasm with adaptive traits for drought resistance, high yields, and grain quality in target environments [23][24][25]. No such comprehensive studies have been carried out to identify donor genotypes with adaptive traits in both irrigated and drought environments in cultivars of Egyptian origin [26].…”
Section: Introductionmentioning
confidence: 99%
“…The stable cultivars usually express better yields and have high adaptability across a wide range of environments. Therefore, evaluating different genotypes across different environments or growing seasons helps to identify donor germplasm with adaptive traits for drought resistance, high yields, and grain quality in target environments [23][24][25]. No such comprehensive studies have been carried out to identify donor genotypes with adaptive traits in both irrigated and drought environments in cultivars of Egyptian origin [26].…”
Section: Introductionmentioning
confidence: 99%
“…Variation for panicle number, panicle length and test weight was significant in soil moisture stress conditions. Results by Ruth et al (2017) revealed significant variation among four environments including drought stress whereas, GXE interaction was non-significant for all the traits except tiller number, grains per panicle and harvest index. Hence, there was no environmental influence on the stability of genotypes, indicating tolerance in general.…”
Section: Discussionmentioning
confidence: 87%